Evaluation and Treatment of Pain in Fetuses, Neonates and Children - Santiago Mencía; Clara Alonso; Carmen Pallás-Alonso; Jesús López-Herce; Maternal and Child Health and Development Network II (SAMID II) (MDPI AG, 2022)
The perception of pain is individual and differs between children and adults. The structures required to feel pain are developed at 24 weeks of gestation. However, pain assessment is complicated, especially in neonates, infants and preschool-age children. Clinical scales adapted to age are the most used methods for assessing and monitoring the degree of pain in children. They evaluate several behavioral and/or physiological parameters related to pain. Some monitors detect the physiological changes that occur in association with painful stimuli, but they do not yet have a clear clinical use. Multimodal analgesia is recommended for pain treatment with non-pharmacological and pharmacological interventions. It is necessary to establish pharmacotherapeutic protocols for analgesia adjusted to the acute or chronic, type and intensity of pain, as well as age. The most used analgesics in children are paracetamol, ibuprofen, dipyrone, opioids (morphine and fentanyl) and local anesthetics. Patient-controlled analgesia is an adequate alternative for adolescent and older children in specific situations, such as after surgery. In patients with severe or persistent pain, it is very important to consult with specific pain services.